1995
DOI: 10.1002/gps.930100203
|View full text |Cite
|
Sign up to set email alerts
|

Delirium during the course of clinically diagnosed Alzheimer's disease

Abstract: SUMMARYA retrospective chart review was completed on the 122 cases of CDAD for the period of 1965-1970 identified from a longitudinal study of dementia a t the Mayo Clinic. A psychiatrist assigned DSM-111-R diagnoses based upon the longitudinal description of symptoms detailed in the medical records of the Mayo Clinic hospitals, nursing home visit records and state hospital records.Thirty patients (25%) were found to have an episode of delirium (EOD) during their course of CDAD which occurred during inpatient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Prior studies have shown that patients with dementia who develop delirium have increased rates of hospitalization, institutionalization, and mortality. 6,[13][14][15] In this sample, after adjusting for baseline differences, the change in score on the Blessed IMC prior to an episode of delirium was 2.5 points per year, consistent with prior reported increases in patients with AD of about 3 points per year. [16][17][18] In the delirium group, the relative change in IMC score doubled from 2.5 points per year at baseline to a postdelirium rate of 4.9 points per year.…”
Section: Resultssupporting
confidence: 65%
“…Prior studies have shown that patients with dementia who develop delirium have increased rates of hospitalization, institutionalization, and mortality. 6,[13][14][15] In this sample, after adjusting for baseline differences, the change in score on the Blessed IMC prior to an episode of delirium was 2.5 points per year, consistent with prior reported increases in patients with AD of about 3 points per year. [16][17][18] In the delirium group, the relative change in IMC score doubled from 2.5 points per year at baseline to a postdelirium rate of 4.9 points per year.…”
Section: Resultssupporting
confidence: 65%
“…57-61 In one study of 771 community-dwelling patients with Alzheimer’s disease (AD), after adjustment for confounders, delirium was associated with a greatly increased adjusted risk of death, relative risk of 5.4 (95% CI 2.3-12.5) or institutionalisation, relative risk of 9.3 (95% CI 5.5-15.7). At one year, 21% of those with cognitive decline, 15% of institutionalisations and 6% of deaths were attributable to delirium.…”
Section: Evidence Linking Delirium and Dementiamentioning
confidence: 99%
“…Outcomes for patients with dementia who develop delirium are worse than for those who do not develop this condition 88,89. In addition to showing worse cognitive function, patients with dementia who experience delirium have higher rates of hospitalization, institutionalization and death 101103…”
Section: Discussionmentioning
confidence: 99%